Simulation Modes Of Relay Protection Devices In Networks With Insulated Neutral - Smagulova, K. K.; Iskakov, U. K. (EAI Endorsed Transactions on Energy Web, 2017)
This program was developed as a universal model of typical devices for protecting electrical networks with insulated neutral. Imitation experiments are executed by the design of working operating and emergency modes. It has been established as in real-world conditions with unselective wearing-outs of protecting as possible.
Keywords: the network with the insulated neutral; current protected devices; the model of electrical network with the insulated neutral; operating conditions; nonselective triggering